2005
DOI: 10.1111/j.1464-5491.2005.01528.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Croatian Type 2 diabetic patients: prevalence and risk factors. A Croatian survey from the European Depression in Diabetes (EDID) Research Consortium

Abstract: The obtained data indicate that the prevalence rate in Croatian Type 2 diabetic patients is comparable to findings from other cultural settings. Depressive symptoms can be predicted by psychological rather than disease-related variables. Psychological care for diabetic patients may be necessary to prevent depressive symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
16
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 8 publications
(7 reference statements)
9
16
2
2
Order By: Relevance
“…Nichols and Brown (24) reported that depression is seen two-fold higher in diabetic women than men. It was reported that mean HAD-A and HAD-D scores are higher in woman diabetic patients, there is a significant correlation between gender, depression and anxiety, and female gender is a risk factor for psychiatric symptoms (13,21,22,25). These results are generally consistent with our findings.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Nichols and Brown (24) reported that depression is seen two-fold higher in diabetic women than men. It was reported that mean HAD-A and HAD-D scores are higher in woman diabetic patients, there is a significant correlation between gender, depression and anxiety, and female gender is a risk factor for psychiatric symptoms (13,21,22,25). These results are generally consistent with our findings.…”
Section: Discussionsupporting
confidence: 83%
“…It is noteworthy that psychiatric symptom and disorder rates found in diabetic patients in several studies done worldwide support our results (19,20). In a study about prevalence of depression in diabetic patients, depression prevalence was reported 33% (21). In a study done in Turkey, major depressive disorder was found in 58.9% of diabetic patients according to DSM-IV criteria and in another study, major depressive disorder was reported in 15% of diabetic patients during interview (4,22).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Patients with type 2 diabetes mellitus have a higher risk level for depression and suffer from high levels of emotional stress compared to healthy controls (Schram, Baan & Pouwer, 2009;Kokoszka et al, 2009). Anxiety and fear are the most frequent emotional disorders among diabetic patients, which have been confirmed by the results of many studies (Peyrot & Rubin, 2000;Pibernik-Okanovic et al, 2005;Thomas, et al, 2003). Numerous studies have confirmed that the course of depression in patients with diabetes is more severe, and the relapses of depression episodes are more frequent, especially in patients with unbalanced diabetes.…”
Section: Emotions and Diabetes Mellitussupporting
confidence: 49%
“…Patients with type 2 diabetes mellitus have a higher risk level for depression and suffer from high levels of emotional stress compared to healthy controls (39)(40)(41). Anxiety and fear are the most frequent emotional disorders among diabetic patients, which have been confirmed by the results of many studies (42)(43)(44). Numerous studies have confirmed that the course of depression in patients with diabetes is more severe, and the relapses of depression episodes are more frequent, especially in patients with unbalanced diabetes.…”
mentioning
confidence: 70%